How The Mathematics Learning Involvement of Students in Village - Zafrullah (Mathematics Research and Education Journal, 2023)
This study aimed to describe the mathematics learning involvement of senior high schools at village schools. This research is qualitative research with a phenomenology approach. The research respondent is the mathematics teachers and students. Data collection techniques are observation and interview. Data were analyzed using the approach proposed by Creswell (2014): preparing and defining data, reading the data as a whole, encoding data, defining themes and creating descriptions, linking themes, and interpreting themes. The analysis results show that the reason students are less involved in learning mathematics; 1) the students feel too difficult to learn mathematics because students don’t understand the teachers' explanation about mathematics, 2) mathematics learning isn’t interesting learning because difficult, still using conventional leaning and no learning media is used; 3) the learning mathematics don’t give the best learning experience to students.